Smoking-related interstitial fibrosis (SRIF) and pulmonary hypertension. (11th March 2013) - El-Kersh, Karim; Perez, Rafael L; Smith, J Shaun; Fraig, Mostafa
Abstract : Smoking-related interstitial fibrosis (SRIF) is a relatively new term used to describe chronic interstitial fibrosis that can develop in smokers. The association of SRIF with pulmonary hypertension has not been described. We present a 55-year-old man with an extensive smoking history who presented for evaluation of insidious onset of dyspnoea on exertion and hypoxaemic respiratory failure. Physical examination was unremarkable. Pulmonary function testing demonstrated a marked reduction of the diffusion capacity with no obstruction or restriction. Ventilation perfusion scan showed no evidence of thromboembolic disease. High-resolution chest CT revealed minimal biapical pleural parenchymal scarring and subtle dependent atelectasis. Serological markers for connective tissue diseases were negative. Open lung biopsy was consistent with SRIF. Vascular intimal proliferation consistent with pulmonary hypertension was also noted. Right heart catheterisation yielded mild pulmonary hypertension and treatment was initiated with tadalafil and bosentan.